Effects of environmental transition on the diversity of arctic soil bacteria / Lim Poh Poh @ Judy - Judy Lim , Poh Poh (2019)
The Arctic is currently one of the most rapidly warming regions on Earth. Soil microbial communities play important roles in various ecological processes in the Arctic. Understanding how the microbial elements in Arctic soil communities are affected by climatic warming is of great concern and has been receiving increasing research attention. To date, there remains a lack of research findings which combine effects of soil warming and water availability on the High Arctic soil microbial community, despite the generally recognised significance of water impacts on soil microbial communities. The projected increase in freeze-thaw (FT) cycle frequency associated with warmer temperatures in the High Arctic could also affect the dynamics of soil bacterial communities. However, there are few studies of the impacts of FT cycles on microbial communities and diversity in the High Arctic. In this study, the first objective was to gain an understanding of the inter-seasonal dynamics of natural soil bacterial diversity at a High Arctic site near Ny-Ålesund, Svalbard, as part of a long-term field environmental manipulation study investigating the impacts of increased soil temperature and water availability on soil microbial communities. The manipulation experiment, using open-top chambers (OTC), was installed in the late summer of 2014, with the soils studied being sampled after snow melt in July 2015, and at the end of the boreal summer in September 2015 and September 2016. Analysis of high throughput sequencing of the 16S rRNA gene on the Illumina MiSeq platform showed a seasonal shift in bacterial community diversity but revealed no significant treatment effects of the open-top chamber warming and/or water addition on bacterial community diversity over the period of the manipulation. The second objective docmented the effects of FT cycles on High Arctic bacterial communities in soil samples collected under three different snow cover depths. Analysis of 16S rRNA gene amplicon The Arctic is currently one of the most rapidly warming regions on Earth. Soil microbial communities play important roles in various ecological processes in the Arctic. Understanding how the microbial elements in Arctic soil communities are affected by climatic warming is of great concern and has been receiving increasing research attention. To date, there remains a lack of research findings which combine effects of soil warming and water availability on the High Arctic soil microbial community, despite the generally recognised significance of water impacts on soil microbial communities. The projected increase in freeze-thaw (FT) cycle frequency associated with warmer temperatures in the High Arctic could also affect the dynamics of soil bacterial communities. However, there are few studies of the impacts of FT cycles on microbial communities and diversity in the High Arctic. In this study, the first objective was to gain an understanding of the inter-seasonal dynamics of natural soil bacterial diversity at a High Arctic site near Ny-Ålesund, Svalbard, as part of a long-term field environmental manipulation study investigating the impacts of increased soil temperature and water availability on soil microbial communities. The manipulation experiment, using open-top chambers (OTC), was installed in the late summer of 2014, with the soils studied being sampled after snow melt in July 2015, and at the end of the boreal summer in September 2015 and September 2016. Analysis of high throughput sequencing of the 16S rRNA gene on the Illumina MiSeq platform showed a seasonal shift in bacterial community diversity but revealed no significant treatment effects of the open-top chamber warming and/or water addition on bacterial community diversity over the period of the manipulation. The second objective docmented the effects of FT cycles on High Arctic bacterial communities in soil samples collected under three different snow cover depths. Analysis of 16S rRNA gene amplicon